Energy potential of the microalgae Oedogonium sp. in production of solid biofuels - Marreiro, Hívila Maria Pontes; Oliveira, Andressa Sales de; Lopes, Riuzuani Michelle Bezerra Pedrosa (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
Renewable energies arise as a way of mitigating the environmental damages caused by traditional of energy sources, as well as offering a diversification of the energy matrix. Among the many energetic vectors possible, microalgae are a good choice for power generation due to their high conversion capacity of solar energy into chemical energy, broadening the possibilities of obtaining algal biomass in energetic applications. Through them, it's possible to produce biodiesel, bioethanol, methane gas and hydrogen gas as fuel. The present work evaluates the energy potential of the microalga Oedogonium sp. through its physical-chemical analysis and the calorific value, as well as the viability of its densification in the form of pellets, to be used as a solid combustion material. For this, calorimetric, thermogravimetric and immediate analyzes were performed, where in the latter it was possible to obtain the moisture, ash, fixed carbon and volatile contents present in the biomass. The results found in the analyzes were satisfactory, in which the higher calorific value was 16,13 MJ/kg, higher than that found for firewood, and in the standards imposed by European, Swedish and international standards for pellets.